Conservation agriculture and maize production risk: The case of Mozambique smallholders - Thierfelder, Christian L.; Kidane, S.; Lambert, D.; Eash, Neal S.; Roberts, R. (Wiley, 2019)
Farming systems in southern Africa are characterized by substantial exposure to external risks to crop production. Compounding these external risks are the effects of climate change, soil degradation, and soil fertility decline that mandates developing sustainable intensification practices to address these issues. In 17 target communities of central Mozambique from 2008–2011, we evaluated the performance of conservation agriculture practices (CAPs) to assess the risk perceptions of smallholder farmers regarding these technologies. The study used the results from 638 farms representing three agro-ecological regions. Net returns were generated for each practice and compared using non-parametric procedures. Risk-preferred technologies were identified using mean-variance, stochastic dominance, and stochastic efficiency with respect to risk function criterion. The results suggest that maize yields were higher for the CAPs systems at low and high elevation sites as compared with conventional tillage practices. Yield variability was also lower in higher elevation areas. At higher elevations, direct seeding was risk-preferred, ranking higher by risk-averse farmers than conventional tillage practices. Risk preferences were ambiguous at lower elevations. However, defining producer utility with a power utility function allowed for comparisons of the technologies over a range of risk-aversion levels. At intermediate and higher altitudes, the direct seeding technology dominated the basin and conventional tillage practices.In low altitudes, and assuming producers were extremely risk-averse, the conventional practice might be preferred over CAP technologies. These findings have implications with respect to selecting areas where CAPs are known to out-perform conventional tillage systems before outscaling technology transferprograms to smallholders.